Dual-earner couples' willingness to relocate abroad: the reciprocal influence of both partners' career role salience and partner role salience. Issue 2 (4th March 2017) - van der Velde, Mandy E. G.; Jansen, Paul G. W.; Bal, P. Matthijs; van Erp, Kim J. P. M.
ABSTRACT: Successful international assignments are important for international organizations. Research has shown that employee willingness to relocate internationally strongly depends on spouse's willingness to follow. However, the mechanisms driving these effects are not thoroughly investigated. This study gives more insight into the processes that explain both partners' willingness to (co-)relocate internationally. We examine the influence of both partners' career role and partner role salience on each other's (co-)relocation willingness. On the basis of Identity theory, Interdependency theory, and Attachment theory, we hypothesize combined interaction effects of career and partner role salience. Data were collected from 226 couples (professional employees and their spouses) working in a multinational Anglo-Dutch company. Results show that, in particular, spouses' willingness to follow their partners abroad is determined by both career importance and partner role salience. We conclude that, for theory and for organizational practice, it is indeed crucial to involve both the employees and their spouses in the decision-making for an international relocation.